Prevalence and types of childhood trauma in first episode psychosis patients. Relation with clinical onset variables. (February 2022) - Vila-Badia, R.; Del Cacho, N.; Butjosa, A.; Serra Arumí, C.; Esteban Santjusto, M.; Abella, M.; Cuevas-Esteban, J.; Morelló, G.; Pardo, M.; Muñoz-Samons, D.; Usall, Judith; ,; et al.
Abstract: Objective: To study the prevalence and the type of childhood trauma (CT) in a first-episode psychosis (FEP) cohort and in a healthy control (HC) sample. To study which clinical and sociodemographic variables in the onset of the FEP are related to having suffered some traumatic experience in childhood. Method: 100 FEP patients and 94 HC participated in the study. The Childhood Traumatic Questionnaire (CTQ) was used to evaluate CT. The Positive and Negative Syndrome Scale (PANSS), the Personal and Social Performance (PSP), the Suicide Risk Scale of Plutchik (SRSP), and the Perceived Stress Scale (PSS) were also administered. Results: 61% of FEP patients and 17% of HC reported having experienced some kind of CT. FEP showed more CT than controls in all subscales, except in sexual abuse. The most frequent CT was emotional abuse. For the FEP group, younger age, more years of education, have a first-degree family history, more positive and negative symptoms, more perceived stress and more personal and social functioning were the variables more influenced by having suffered some kind of CT. Conclusions: There is a high prevalence of CT in FEP patients. Having a first-degree family history of mental illness, more positive symptoms, and more perception of stress at the time of hospital admission were related to having suffered CT. More research is needed to find out the best way to detect CT and its role in psychosis to be able to implement interventions to improve the evolution of these patients.